Ultra-high density consolidation plugging agent and preparation method thereof, and diluent and preparation method and application thereof

By introducing coating weighting agent and terpolymer diluent into the drilling plugging agent, the existing plugging agent has solved the problem of poor fluidity and low strength in the high-pressure leakage formation, achieving high density, low viscosity, good pumping and high consolidation strength, and improving leakage plugging efficiency and economic benefits.

CN119331153BActive Publication Date: 2025-03-25SOUTHWEST PETROLEUM ENG CO LTD SINOPEC +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411894709.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-25
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

When used in high-pressure leakage plugging formations, the existing drilling leak plugging agent has poor fluidity, low strength and poor condensation, resulting in repeated leakage loss and well control risks. The leakage plugging material consumes a large amount and the leakage plugging time is long, which affects economic benefits.

Method used

The ultra-high density consolidation plugging agent is adopted to improve the density, viscosity control and pumpable performance of the plugging agent by introducing coating weighting agents and self-developed terpolymer diluents, and enhance the consolidation strength and bridge filling ability.

Benefits of technology

The high density, low viscosity, good pumping and high consolidation strength of the leak plugging agent are achieved, which reduces the bottom-hole pressure difference, avoids repeated leakage loss and well control risks, and improves leakage plugging efficiency and economic benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention discloses an ultra-high density consolidation plugging agent and a preparation method thereof, a diluent and a preparation method and application thereof, and belongs to the technical field of plugging for drilling. The diluent is a terpolymer polymerized in water by 3-butene-1-ol, sodium p-styrene sulfonate, and methacryloyloxyethyl trimethyl ammonium chloride in the presence of ammonium sulfate; the ultra-high density consolidation plugging agent, in parts by mass, includes: 80 to 100 parts of water; 80 to 100 parts of curing agent; 10 to 30 parts of activator; 0.3 to 2 parts of diluent; 0.1 to 3 parts of retarder; 85 to 335 parts of coating weighting agent; and 0.2 to 1 part of fiber. The present invention can increase the upper limit of weighting by introducing a coating weighting agent, so that the density of the ultra-high density consolidation plugging agent can be as high as 2.7g / cm 3 , and by introducing the self-developed terpolymer as a diluent, the viscosity of the ultra-high density consolidation plugging agent can be effectively reduced and the circulation pressure can be reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a plugging agent for drilling and a preparation method thereof, in particular to an ultra-high density consolidation plugging agent and a preparation method thereof, a diluent and a preparation method and application thereof. Background Art

[0002] As oil and gas exploration and development expands into deep, ultra-deep and unconventional oil and gas resources, drilling projects are faced with more demanding geological conditions and many technical bottlenecks. Malignant well leakage in fractured (fracture-cavity) formations is one of the most common and most difficult to control complex accidents in drilling projects.

[0003] According to statistics, the incidence of well leakage in the global oil industry is about 20% to 25%, and the annual cost of well leakage is as high as US$2 billion to US$4 billion, of which serious well leakage losses account for more than 70%.

[0004] The deep gas reservoirs in the Sichuan-Chongqing region are characterized by one super, three highs, and five complexities. They are one of the deepest, most risky, and most difficult oil and gas exploration and development blocks in the world. When drilling into a high-pressure leakage formation, conventional plugging agents are generally used to add weight to crystal powder for plugging, or high-density cement slurry is used for plugging, assisted by bridge plugging agents. Although these plugging agents have achieved certain results in the field, they also have the following disadvantages or shortcomings: ① After weighting, they can meet the high-density requirements, but the fluidity is not good, the strength is low, and the coagulation is not good; the solid phase is high, the viscosity is high, the circulation pressure is high, and repeated leakage is easy to occur; ② The high-density cement slurry has low viscosity and poor hysteresis capacity, and the volume is easy to shrink during plugging, and free water is easy to appear; ③ The plugging material consumption is large and the plugging time is long; when encountering a high-pressure leakage formation, a high concentration of bridge plugging agent is added to the high-solid plugging slurry, and the plugging slurry is difficult to enter the deep channel of the high-pressure leakage fracture and is easy to seal; ④ The plugging slurry has poor coagulation and low strength, resulting in temporary plugging, leading to repeated plugging, causing great economic losses, and directly affecting the plugging effect and drilling engineering. Summary of the invention

[0005] The purpose of the present invention is to provide an ultra-high density consolidation plugging agent and a preparation method thereof to solve the above problems. The ultra-high density consolidation plugging agent of the present invention has small particle size, high density, low viscosity, good pumpability, good crack matching, strong retention capacity, and high consolidation strength. The shortcomings or deficiencies existing in the above-mentioned prior art are effectively overcome or avoided. The purpose of the present invention is also to provide a diluent and a preparation method and application thereof.

[0006] The present invention achieves the above-mentioned purpose through the following technical solutions:

[0007] A diluent is a terpolymer formed by polymerizing 3-butene-1-ol, sodium p-styrene sulfonate and methacryloyloxyethyl trimethyl ammonium chloride in water in the presence of ammonium sulfate, wherein the mass ratio of 3-butene-1-ol to sodium p-styrene sulfonate is 1:0.1-0.6, the mass fraction of methacryloyloxyethyl trimethyl ammonium chloride is 1%-4% of the total mass of 3-butene-1-ol and sodium p-styrene sulfonate, the amount of water added makes the mass concentration of the reactant 40%-60%, the amount of ammonium sulfate added is 1%-4% of the total mass of 3-butene-1-ol, sodium p-styrene sulfonate and methacryloyloxyethyl trimethyl ammonium chloride, and the reactant is a substance obtained by mixing 3-butene-1-ol, sodium p-styrene sulfonate and methacryloyloxyethyl trimethyl ammonium chloride.

[0008] The diluent is a terpolymer with a sulfonic acid group, an amide group, a quaternary ammonium group and a hydroxyl group on the side chain.

[0009] The molecular formula of the diluent is:

[0010]

[0011] In the molecular formula, x, y, and z are all natural numbers, and the range of x:y:z is 1~20:1~10:1~50.

[0012] A method for preparing the diluent comprises the following steps:

[0013] Step 1, adding 3-butene-1-ol and sodium p-styrene sulfonate into a reaction kettle; then adding methacryloyloxyethyl trimethylammonium chloride to obtain a reactant; and then adding water to the reactant;

[0014] Step 2, adding ammonium sulfate as an initiator to the reactant after adding water in step 1; then turning on the agitator, passing nitrogen for 30 to 120 minutes to exhaust the air in the reactor, heating the reaction system to 75 to 85° C. to start the polymerization reaction; maintaining the reaction under nitrogen atmosphere for 4 to 8 hours to obtain the diluent.

[0015] An application of the diluent in a plugging agent.

[0016] An ultra-high density consolidation plugging agent comprises, by weight: 80 to 100 parts of water; 80 to 100 parts of a curing agent; 10 to 30 parts of an activator; 0.3 to 2 parts of the diluent; 0.1 to 3 parts of a retarder; 85 to 335 parts of a coating weighting agent; and 0.2 to 1 part of fiber.

[0017] The coated weighting agent is a product obtained by coating a mixture of submicron barium sulfate, API standard barite and ilmenite.

[0018] The preparation method of the film-coated weighting agent comprises the following steps:

[0019] S1, adding submicron barium sulfate, API standard barite, and ilmenite in a mass ratio of 4:5:1 into a reactor and stirring and mixing for at least 3 hours to obtain a mixture; wherein the particle size of the submicron barium sulfate is distributed in the range of 1 to 10 μm, and the density is 4.3 g / cm 3 ; API standard barite particle size distribution is 10 ~ 100μm, density is 4.3g / cm 3 ; The particle size of ilmenite is above 100 μm and the density is 5.05 g / cm 3 ;

[0020] S2, putting the obtained mixture into a coating reaction kettle, adding stearic acid amide, stirring at 130° C. for at least 2 hours, and then cooling to obtain a coating weighting agent; wherein the mass ratio of the mixture to stearic acid amide is 10:1-3.

[0021] The curing agent is at least one of oil well cement, blast furnace slag, and fly ash; the activator is at least one of NaOH and KOH; the retarder is at least one of sodium dihydrogen phosphate and high-temperature oil well cement retarder HX-36L; the fiber is at least one of basalt fiber and brucite fiber.

[0022] A preparation method of the ultra-high density consolidation plugging agent comprises the following steps: adding water, curing agent, activator, diluent, retarder, coating weighting agent and fiber into a mixer according to their proportions, and stirring and mixing them evenly under normal pressure and temperature to obtain the ultra-high density consolidation plugging agent.

[0023] Compared with the prior art, the beneficial technical effects of the present invention are:

[0024] The invention can increase the upper limit of the weighting of the ultra-high density consolidation plugging agent by introducing a coating weighting agent, so that the density of the ultra-high density consolidation plugging agent can be as high as 2.7g / cm 3 . And by introducing the self-developed terpolymer as a diluent, the viscosity of the ultra-high density consolidation plugging agent can be effectively controlled, the circulation pressure can be reduced, and the pumpability can be improved.

[0025] The ultra-high density consolidation plugging agent provided by the present invention has simple plugging construction, which can be mixed evenly in proportion on site and pumped into the leaking layer through a mud pump. The ultra-high density consolidation plugging agent provided by the present invention has adjustable density, which can be calculated according to the on-site leakage pressure and the density can be controlled within 2.0-2.7 g / cm by adjusting the component ratio. 3The ultra-high density consolidation plugging agent provided by the present invention has high curing strength, a bottom hole temperature of 70-150°C, a curing time of 24 hours, a compressive strength of the consolidation body greater than 7MPa, and an adjustable thickening time, which meets the requirements of plugging and pressure plugging operations. The ultra-high density consolidation plugging agent provided by the present invention has high thixotropy, has obvious structural strength when standing still, and has bridging filling ability. DETAILED DESCRIPTION

[0026] The preferred embodiments of the present invention are described below. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0027] Example 1-Example 7

[0028] A method for preparing an ultra-high density consolidation plugging agent of the present invention comprises the following steps:

[0029] Water, curing agent, activator, diluent, retarder, coating weighting agent, and fiber are added into a mixer according to their proportions, and stirred and mixed evenly under normal pressure and temperature to obtain an ultra-high density consolidation plugging agent. The specific proportions of water, curing agent, activator, diluent, retarder, coating weighting agent, and fiber are shown in Table 1.

[0030] Table 1 Component ratios of ultra-high density consolidation plugging agents of Examples 1 to 7

[0031]

[0032] Note: “ / ” in Table 1 means that the corresponding component is not added.

[0033] In Examples 1 to 7, the coated weighting agent is a product obtained by coating a mixture of submicron barium sulfate, API standard barite and ilmenite.

[0034] In Example 1 to Example 7, the preparation method of the film-coated weighting agent comprises the following steps:

[0035] S1, adding submicron barium sulfate, API standard barite, and ilmenite in a mass ratio of 4:5:1 into a reactor and stirring and mixing for at least 3 hours to obtain a mixture; wherein the particle size of the submicron barium sulfate is distributed in the range of 1 to 10 μm, and the density is 4.3 g / cm 3 ; API standard barite particle size distribution is 10 ~ 100μm, density is 4.3g / cm 3 ; The particle size of ilmenite is above 100 μm and the density is 5.05 g / cm 3 ;

[0036] S2, putting the obtained mixture into a coating reaction kettle, adding stearic acid amide, stirring at 130° C. for at least 2 hours, and then cooling to obtain a coating weighting agent; wherein the mass ratio of the mixture to stearic acid amide is 10:1-3.

[0037] In Examples 1 to 7, the diluent is a terpolymer having a sulfonic acid group, an amide group, a quaternary ammonium group and a hydroxyl group on the side chain.

[0038] In Example 1 and Example 2, the diluent is a terpolymer polymerized by 3-butene-1-ol, sodium p-styrene sulfonate, and methacryloyloxyethyl trimethyl ammonium chloride in water in the presence of ammonium sulfate, wherein the mass ratio of 3-butene-1-ol to sodium p-styrene sulfonate is 1:0.1, the mass fraction of methacryloyloxyethyl trimethyl ammonium chloride is 1% of the total mass of 3-butene-1-ol and sodium p-styrene sulfonate, the amount of water added is such that the mass concentration of the reactants is 40%, the amount of ammonium sulfate added is 1% of the total mass of 3-butene-1-ol, sodium p-styrene sulfonate and methacryloyloxyethyl trimethyl ammonium chloride, and the reactants are a substance obtained by mixing 3-butene-1-ol, sodium p-styrene sulfonate and methacryloyloxyethyl trimethyl ammonium chloride; the preparation method of the diluent comprises the following steps:

[0039] Step 1, adding 3-butene-1-ol and sodium p-styrene sulfonate into a reaction kettle, and then adding methacryloyloxyethyl trimethylammonium chloride to obtain a reactant; and then adding water to the reactant;

[0040] Step 2, adding ammonium sulfate as an initiator to the reactant after adding water in step 1, then turning on the agitator, passing nitrogen for 30 minutes to exhaust the air in the reactor, heating the reaction system to 75°C to start the polymerization reaction; maintaining the reaction under nitrogen atmosphere for 4 hours to obtain the diluent.

[0041] In Example 3 and Example 4, the diluent is a terpolymer polymerized by 3-butene-1-ol, sodium p-styrene sulfonate, and methacryloyloxyethyl trimethyl ammonium chloride in water in the presence of ammonium sulfate, wherein the mass ratio of 3-butene-1-ol to sodium p-styrene sulfonate is 1:0.3, the mass fraction of methacryloyloxyethyl trimethyl ammonium chloride is 2% of the total mass of 3-butene-1-ol and sodium p-styrene sulfonate, the amount of water added is such that the mass concentration of the reactants is 50%, the amount of ammonium sulfate added is 2% of the total mass of 3-butene-1-ol, sodium p-styrene sulfonate and methacryloyloxyethyl trimethyl ammonium chloride, and the reactants are a substance obtained by mixing 3-butene-1-ol, sodium p-styrene sulfonate and methacryloyloxyethyl trimethyl ammonium chloride; the preparation method of the diluent comprises the following steps:

[0042] Step 1, adding 3-butene-1-ol and sodium p-styrene sulfonate into a reaction kettle, and then adding methacryloyloxyethyl trimethylammonium chloride to obtain a reactant; and then adding water to the reactant;

[0043] Step 2, adding ammonium sulfate as an initiator to the reactant after adding water in step 1, then turning on the agitator, passing nitrogen for 60 minutes to exhaust the air in the reactor, heating the reaction system to 80° C. to start the polymerization reaction; maintaining the reaction under nitrogen atmosphere for 5 hours to obtain the diluent.

[0044] In Example 5 and Example 6, the diluent is a terpolymer polymerized by 3-butene-1-ol, sodium p-styrene sulfonate, and methacryloyloxyethyl trimethyl ammonium chloride in water in the presence of ammonium sulfate, wherein the mass ratio of 3-butene-1-ol to sodium p-styrene sulfonate is 1:0.6, the mass fraction of methacryloyloxyethyl trimethyl ammonium chloride is 4% of the total mass of 3-butene-1-ol and sodium p-styrene sulfonate, the amount of water added is such that the mass concentration of the reactants is 60%, the amount of ammonium sulfate added is 4% of the total mass of 3-butene-1-ol, sodium p-styrene sulfonate and methacryloyloxyethyl trimethyl ammonium chloride, and the reactants are a substance obtained by mixing 3-butene-1-ol, sodium p-styrene sulfonate and methacryloyloxyethyl trimethyl ammonium chloride; the preparation method of the diluent comprises the following steps:

[0045] Step 1, adding 3-butene-1-ol and sodium p-styrene sulfonate into a reaction kettle, and then adding methacryloyloxyethyl trimethylammonium chloride to obtain a reactant; and then adding water to the reactant;

[0046] Step 2, adding ammonium sulfate as an initiator to the reactant after adding water in step 1, then turning on the agitator, passing nitrogen for 90 minutes to exhaust the air in the reactor, heating the reaction system to 85° C. to start the polymerization reaction; maintaining the reaction under nitrogen atmosphere for 6 hours to obtain the diluent.

[0047] In Example 7, the diluent is a terpolymer polymerized by 3-butene-1-ol, sodium p-styrene sulfonate, and methacryloyloxyethyl trimethyl ammonium chloride in water in the presence of ammonium sulfate, wherein the mass ratio of 3-butene-1-ol to sodium p-styrene sulfonate is 1:0.4, the mass fraction of methacryloyloxyethyl trimethyl ammonium chloride is 3% of the total mass of 3-butene-1-ol and sodium p-styrene sulfonate, the amount of water added is such that the mass concentration of the reactants is 55%, the amount of ammonium sulfate added is 3% of the total mass of 3-butene-1-ol, sodium p-styrene sulfonate and methacryloyloxyethyl trimethyl ammonium chloride, and the reactants are a substance obtained by mixing 3-butene-1-ol, sodium p-styrene sulfonate and methacryloyloxyethyl trimethyl ammonium chloride; the preparation method of the diluent comprises the following steps:

[0048] Step 1, adding 3-butene-1-ol and sodium p-styrene sulfonate into a reaction kettle; then adding methacryloyloxyethyl trimethylammonium chloride to obtain a reactant; and then adding water to the reactant;

[0049] Step 2, adding ammonium sulfate as an initiator to the reactant after adding water in step 1; then turning on the agitator, passing nitrogen for 120 minutes to exhaust the air in the reactor, heating the reaction system to 80° C. to start the polymerization reaction; maintaining the reaction under nitrogen atmosphere for 8 hours to obtain the diluent.

[0050] The diluent in Examples 1 to 7 is a terpolymer having a sulfonic acid group, an amide group, a quaternary ammonium group and a hydroxyl group on the side chain.

[0051] The diluents in Examples 1 to 7 can be used not only in the ultra-high density consolidation plugging agent of the present invention, but also in other plugging agents.

[0052] The 3-butene-1-ol, sodium p-styrene sulfonate, methacryloyloxyethyl trimethylammonium chloride and ammonium sulfate used in the preparation process of the diluent are all chemically pure and purchased from Chengdu Kelong Chemical Co., Ltd.

[0053] In Examples 1 to 7, the molecular formula of the diluent is:

[0054]

[0055] In the molecular formula, x, y, and z are all natural numbers, and the range of x:y:z is 1~20:1~10:1~50.

[0056] In Examples 1 to 7, the high temperature oil well cement retarder HX-36L was purchased as a finished product from Chengdu OMEC Petroleum Technology Co., Ltd.

[0057] Comparative Example 1-Comparative Example 7

[0058] A method for preparing a consolidation plugging agent according to Comparative Examples 1 to 7 comprises the following steps:

[0059] Water, curing agent, activator, retarder, coating weighting agent, and fiber are added into a mixer according to their proportions, and stirred and mixed evenly under normal pressure and temperature to obtain a consolidation plugging agent. The specific proportions of water, curing agent, activator, retarder, coating weighting agent, and fiber are shown in Table 2.

[0060] Table 2 Component ratios of the consolidation plugging agents of Comparative Examples 1 to 7

[0061]

[0062] Note: “ / ” in Table 2 means that the corresponding component is not added.

[0063] Comparative Example 8-Comparative Example 14

[0064] A method for preparing a consolidation plugging agent according to Comparative Examples 8 to 14 comprises the following steps:

[0065] Water, curing agent, activator, diluent, retarder, weighting agent without film coating, and fiber are added into a mixer according to their respective proportions, and stirred and mixed evenly under normal pressure and room temperature to obtain an ultra-high density consolidation plugging agent. The specific proportions of water, curing agent, activator, diluent, retarder, weighting agent without film coating, and fiber are shown in Table 3.

[0066] Table 3 Component ratios of consolidation plugging agents of Comparative Examples 8 to 14

[0067]

[0068] Note: “ / ” in Table 3 means that the corresponding component is not added.

[0069] The uncoated weighting agent in Comparative Examples 8 to 14 is a mixture of submicron barium sulfate, API standard barite, and ilmenite in a mass ratio of 4:5:1, obtained by mixing without coating treatment.

[0070] In Comparative Examples 8 to 14, the preparation method of the weighting agent without coating comprises the following steps: adding submicron barium sulfate, API standard barite, and ilmenite in a mass ratio of 4:5:1 into a reactor and stirring and mixing for at least 3 hours to obtain a mixture; wherein the particle size distribution of submicron barium sulfate is 1 to 10 μm, and the density is 4.3 g / cm 3 ; API standard barite particle size distribution is 10 ~ 100μm, density is 4.3g / cm 3 ; The particle size of ilmenite is above 100 μm and the density is 5.05 g / cm 3 .

[0071] The performance of the ultra-high density consolidation plugging agents prepared in Examples 1 to 7 is tested below.

[0072] The thickening time and compressive strength (5×5×5cm2) of the ultra-high density consolidation plugging agent prepared by the preparation methods of Examples 1 to 7 at different densities and curing temperatures were measured. 3 The test method is in accordance with the national standard GB / T 19139-2012 “Test methods for oil well cement”. The test results are shown in Table 4.

[0073] The rheological properties of the ultra-high density consolidation plugging agents prepared by Examples 1 to 7 and the consolidation plugging agents prepared by the preparation methods of Comparative Examples 1 to 7 and Comparative Examples 8 to 14 were tested to examine their pumpability. The experimental instrument used was a ZNN-D6 six-speed rotary viscometer. The experimental method was carried out in accordance with the national standard GB / T 16783.1-2014 drilling fluid field test. The test results are shown in Tables 5 and 6.

[0074] Table 4 Performance indexes of ultra-high density consolidation plugging agents prepared in Examples 1 to 7

[0075] project <![CDATA[Density (g / cm 3 )]]> Experimental temperature (℃) Thickening time (min) Compressive strength (MPa) Example 1 2.0 70 188 7.0 Example 2 2.10 90 420 8.0 Example 3 2.20 130 362 9.8 Example 4 2.35 150 136 10.1 Example 5 2.50 140 198 11.3 Example 6 2.60 120 156 12.6 Example 7 2.70 120 173 14.6

[0076] Table 5 Rheological properties of the ultra-high density consolidation plugging agents prepared in Examples 1 to 7 and the rheological properties of the consolidation plugging agents prepared in Comparative Examples 1 to 7

[0077] project φ600 φ300 φ200 φ100 φ6 φ3 Example 1 97 54 41 28 12 11 Example 2 112 88 54 41 14 13 Example 3 148 93 67 52 16 15 Example 4 189 103 78 65 20 18 Example 5 220 127 99 74 22 19 Example 6 251 154 121 87 24 22 Example 7 280 185 156 125 25 24 Comparative Example 1 230 175 147 122 51 49 Comparative Example 2 288 202 163 131 55 52 Comparative Example 3 Over range 267 189 157 56 55 Comparative Example 4 Over range 298 200 161 60 57 Comparative Example 5 Over range Over range 224 199 63 62 Comparative Example 6 Over range Over range 259 223 65 62 Comparative Example 7 Over range Over range 286 251 68 65

[0078] Note: The data in Table 5 are all tested at room temperature.

[0079] Table 6 Rheological properties of the ultra-high density consolidation plugging agents prepared in Examples 1 to 7 and the rheological properties of the consolidation plugging agents prepared in Comparative Examples 8 to 14

[0080] project φ600 φ300 φ200 φ100 φ6 φ3 Example 1 97 54 41 28 12 11 Example 2 112 88 54 41 14 13 Example 3 148 93 67 52 16 15 Example 4 189 103 78 65 20 18 Example 5 220 127 99 74 22 19 Example 6 251 154 121 87 24 22 Example 7 280 185 156 125 25 24 Comparative Example 8 185 105 86 73 32 31 Comparative Example 9 234 141 133 94 44 42 Comparative Example 10 267 192 166 123 46 43 Comparative Example 11 298 206 187 149 58 57 Comparative Example 12 Over range 277 203 170 60 58 Comparative Example 13 Over range Over range 245 205 63 62 Comparative Example 14 Over range Over range 279 214 65 64

[0081] As shown in Table 4, the density of the ultra-high density consolidation plugging agent can be controlled within the range of 2.0-2.7 g / cm by adjusting the proportion of the ingredients. 3 The experimental temperature is 70-150℃, the thickening time is adjustable between 146-420min, the curing time is 24h, and the compressive strength of the consolidated body is greater than 7MPa.

[0082] It can be seen from Table 5 that, by comparing the experimental data of Example 1 with Comparative Example 1, Example 2 with Comparative Example 2, Example 3 with Comparative Example 3, Example 4 with Comparative Example 4, Example 5 with Comparative Example 5, Example 6 with Comparative Example 6, and Example 7 with Comparative Example 7, under the same experimental conditions, Comparative Examples 1 to Comparative Examples 7 did not use a diluent, and the rheological properties of Comparative Examples 1 to Comparative Examples 7 were poor and the pumping was extremely difficult, while Examples 1 to 7 respectively added different amounts of diluents and coating weighting agents, and the overall rheological properties were good and the pumpability was good.

[0083] It can be seen from Table 6 that, by comparing the experimental data of Example 1 and Comparative Example 8, Example 2 and Comparative Example 9, Example 3 and Comparative Example 10, Example 4 and Comparative Example 11, Example 5 and Comparative Example 12, Example 6 and Comparative Example 13, and Example 7 and Comparative Example 14, under the same experimental conditions, Comparative Examples 8 to Comparative Examples 14 did not use a coating weighting agent, and the rheological properties of Comparative Examples 8 to Comparative Examples 14 were also poor, and pumping was extremely difficult, while Examples 1 to 7 added different amounts of diluents and coating weighting agents, respectively, and the overall rheological properties were good and the pumpability was good.

[0084] From Table 5 and Table 6, we can see that the diluent has a greater effect on changing the rheological properties. The use of diluent and coating weighting agent at the same time is the best way to improve the rheological properties of the plugging agent, which can meet the pumping requirements of ultra-high density plugging agents.

Claims

1. A diluent, characterized in that The invention discloses a terpolymer prepared by polymerizing 3-butene-1-ol, sodium p-styrene sulfonate and methacryloyloxyethyl trimethyl ammonium chloride in water in the presence of ammonium sulfate, wherein the mass ratio of 3-butene-1-ol to sodium p-styrene sulfonate is 1:0.1-0.6, the mass fraction of methacryloyloxyethyl trimethyl ammonium chloride is 1%-4% of the total mass of 3-butene-1-ol and sodium p-styrene sulfonate, the amount of water added makes the mass concentration of the reactants 40%-60%, the amount of ammonium sulfate added is 1%-4% of the total mass of 3-butene-1-ol, sodium p-styrene sulfonate and methacryloyloxyethyl trimethyl ammonium chloride, and the reactants are substances obtained by mixing 3-butene-1-ol, sodium p-styrene sulfonate and methacryloyloxyethyl trimethyl ammonium chloride.

2. The diluent according to claim 1, characterized in that: The molecular formula of the diluent is: In the molecular formula, x, y, and z are all natural numbers, and the range of x:y:z is 1~20:1~10:1~50.

3. A method for preparing the diluent according to claim 1 or 2, characterized in that: The steps include: Step 1, adding 3-butene-1-ol and sodium p-styrene sulfonate into a reaction kettle; then adding methacryloyloxyethyl trimethylammonium chloride to obtain a reactant; and then adding water to the reactant; Step 2, adding ammonium sulfate as an initiator to the reactant after adding water in step 1; then turning on the agitator, passing nitrogen for 30 to 120 minutes to exhaust the air in the reactor, heating the reaction system to 75 to 85° C. to start the polymerization reaction; maintaining the reaction under nitrogen atmosphere for 4 to 8 hours to obtain the diluent.

4. Use of the diluent according to claim 1 or 2 in a plugging agent.

5. An ultra-high density consolidation plugging agent, characterized in that: The invention comprises, by weight: 80 to 100 parts of water; 80 to 100 parts of curing agent; 10 to 30 parts of activator; 0.3 to 2 parts of diluent according to claim 1, 2 or 3; 0.1 to 3 parts of retarder; 85 to 335 parts of coating weighting agent; 0.2 to 1 part of fiber; the preparation method of the coating weighting agent comprises the following steps: S1, adding submicron barium sulfate, API standard barite, and ilmenite in a mass ratio of 4:5:1 into a reactor and stirring and mixing for at least 3 hours to obtain a mixture; wherein the particle size of the submicron barium sulfate is distributed in the range of 1 to 10 μm, and the density is 4.3 g / cm 3 ; API standard barite particle size distribution is 10 ~ 100μm, density is 4.3g / cm 3 ; The particle size of ilmenite is above 100 μm and the density is 5.05 g / cm 3 ; S2, putting the obtained mixture into a coating reaction kettle, adding stearic acid amide, stirring at 130° C. for at least 2 hours, and then cooling to obtain a coating weighting agent; wherein the mass ratio of the mixture to stearic acid amide is 10:1-3.

6. The ultra-high density consolidation plugging agent according to claim 5, characterized in that: The coated weighting agent is a product obtained by coating a mixture of submicron barium sulfate, API standard barite and ilmenite.

7. The ultra-high density consolidation plugging agent according to claim 5, characterized in that: The curing agent is at least one of oil well cement, blast furnace slag, and fly ash; the activator is at least one of NaOH and KOH; the retarder is at least one of sodium dihydrogen phosphate and high-temperature oil well cement retarder HX-36L; the fiber is at least one of basalt fiber and brucite fiber.

8. A method for preparing the ultra-high density consolidation plugging agent according to any one of claims 5 to 7, characterized in that: The method comprises the following steps: adding water, curing agent, activator, diluent, retarder, coating weighting agent and fiber into a mixer according to their proportions, and stirring and mixing them evenly under normal pressure and temperature to obtain an ultra-high density consolidation plugging agent.

Citation Information

Patent Citations

  • Method for preparing oil well cement delayed coagulant and application method thereof

    CN106632842A

  • Salt-resistant filtrate reducer at 220-230 DEG C and preparation method thereof

    CN119019602A